Detection of immunoglobulin heavy chain gene rearrangements in Hodgkin's disease using PCR. Issue 10 (October 1993) - Angel, C A; Pringle, J H; Primrose, L; Lauder, I
Abstract : AIM–To detect clonal rearrangements of the immunoglobulin (Ig) heavy chain gene in Hodgkin's disease tissue using the polymerase chain reaction (PCR). METHODS–DNA extracted from 36 samples of Hodgkin's disease was analysed using PCR and primers from conserved sequences in the variable (VH) and joining (JH) regions. RESULTS–Clonal rearrangement was detected only in one case. Evidence of clonal immunoglobulin gene rearrangement had been detected previously in this case using conventional Southern blot analysis. CONCLUSIONS–The sensitivity of the two techniques is equivalent and clonal Ig heavy chain gene rearrangements are rare in Hodgkin's disease.